PENYULUHAN KESEHATAN MENGENAI DISPEPSIA PADA REMAJA DI SMAN 1 KAMPAR - Ade Dita Puteri; Devina Yuristin (Universitas Pahlawan Tuanku Tambusai, 2022)
Complaints of dyspepsia is a clinical condition that is often encountered in daily practice. The term dyspepsia started from being intensively promoted since the late 80s, which describes a complaint or a collection of symptoms (syndrome) consisting of pain or discomfort in the epigastrium, nausea, vomiting, bloating, early satiety, full stomach, belching, and a feeling of discomfort. radiating heat in the chest. Dyspepsia usually begins with bad habits breakfast, breakfast for teenagers, should be useful, because school time is an activity that requires energy and calories are quite large. The negative impact of not having breakfast can be an imbalance in the central nervous system followed by dizziness, shaking, or feeling tired. this can also trigger dyspepsia, because during 12 hours of sleep the body fasts all night, and in the morning it is in the first stage of feeling hungry so that the stomach which is still in the stage can increase stomach acid levels so that it can trigger dyspepsia. The purpose of this community service knowledge is to increase adolescents about dyspepsia and how to prevent dyspepsia. The method used is counseling with lectures, discussions, questions and answers and demos. The results of the 61 adolescents at SMAN 1 Kampar who participated in the counseling found that most of the adolescents were given better counseling after counseling than before counseling about dyspepsia. Keywords: dyspepsia, prevention, symptoms